Comparative Analysis of The Structural-Semantic Aspects of The Concept "Work" In English and Uzbek Proverbs and Sayings - Burxonova Gulrux (Zien Journals, 2024)
This article is devoted to the problems of concept in Modern English and Uzbek. It discusses the structural and semantic features of the concept “work” in compared languages
Keywords: structure; semantic feature; grammar; lexemes